The cyberspace impacts on urban policies - Emília Malcata Rebelo (2004)
This article analyses the effects globalisation and new technology internationalisation exert upon urban and regional economies. A reflection is carried out about the influences exerted by globalisation on Urban Planning and Territorial Management, indicating some difficulties in the integration and coordination of those policies, and in what concerns their territorial expression. The postmodernist trend to segregate different socialities (Hubbard, 2002) is analysed through a case study applied to Portugal, where the social, economic, cultural and religious coexistence of different ethnic groups are analysed, particularly in what concerns spatial distribution of immigrants and ethnic minorities. A concept of bottom up Urban Planning is developed based upon the collection and analysis of different ways of local government, increasingly based on the governance of space (Merry, 2001). Finally, a hedonic model is proposed, that expresses territorial distribution of different population groups as a function of certain objective and subjective variables. This model displays the results of alternative urban policies aimed to better adjust different groups to city features, and it allows the enhancement of a better quality of urban life.